Integral Model For Assessing The Effectiveness Of Women's Intellectual Labor Management In An Innovative Economy - Kizi, Nabikhujayeva Dilafruz Sabir (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The transition toward an innovative economy highlights human capital and intellectual labor as central drivers of economic development. Specific Background Women’s intellectual labor represents a significant yet underutilized resource, requiring systematic management and assessment frameworks. Knowledge Gap Existing studies primarily examine isolated indicators, lacking comprehensive integral models that combine economic, social, and innovative dimensions into a unified evaluation system. Aims This study aims to develop an integral model for assessing the management of women’s intellectual labor using a multifactor and quantitative approach. Results The research formulates an integral index (I = 0.72), indicating an above-average level of management performance, with education and digital skills identified as dominant factors through correlation-regression analysis. The model integrates normalized indicators across employment, income, education, qualifications, research participation, and digital competencies. Novelty The study introduces a structured integral assessment model based on multi-criteria decision-making and statistical methods, enabling systematic aggregation of diverse indicators into a single analytical framework. Implications The findings provide a scientific basis for improving labor market policies, strengthening gender-oriented institutional mechanisms, and supporting strategic decision-making for the development of women’s intellectual potential in an innovative economy. Highlights:• Integral index reveals above-average performance with structured multi-indicator aggregation• Education and digital competencies emerge as dominant determinants in regression results• Model supports policy formulation for labor systems and gender-oriented strategies Keywords: Innovative Economy, Women Intellectual Labor, Integral Model, Human Capital, Correlation Regression Analysis